Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

In a question in Fuhrmann's "A polynomial approach to linear algebra" it is stated that $$\sum_{i=1}^n \frac{p(a_i)}{q'(a_i)}=p_{a_{n-1}},$$ where $p,q$ are polynomials over a field with $deg(p)=n-1$ and $deg(q)=n$. $q(x)$ is also a monic polynomial with the unique factorization $p(x)=(x-a_1)(x-a_2)...(x-a_n)$.

$q'(x)$ is the formal derivative of $q(x)$, and $p_{a_{n-1}}$ is the $n-1$:th coefficient of $p$, i.e. it's leading coefficient.

Does anyone know how to do it?

A tip is to use Langrange interpolation.

share|cite|improve this question
Use Lagrange interpolation for what? Pointer to where? Perhaps you forgot to state that you're interested in proving this statement? – joriki Sep 28 '12 at 11:07
up vote 1 down vote accepted

By Lagrange interpolation, we have \[ p(x) = \sum_{i=1}^n p(a_i) \prod_{j \ne i} \frac{x - a_j}{a_i - a_j} \] As $q(x) = \prod_j (x-a_j)$, we have $q'(x) = \sum_i \prod_{j \ne i} (x-a_j)$, so $q'(a_i) = \prod_{j\ne i} (a_i-a_j)$, and $\prod_{j \ne i} (x-a_j)$ equals $\frac{q(x)}{x-a_i}$, so \[ p(x) = \sum_{i=1}^n \frac{p(a_i)}{q'(a_i)} \cdot \frac{q(x)}{(x-a_i)} \] Looking at the coefficient of $x^{n-1}$, gives, as $\frac{q(x)}{x-a_i}$ is monic \[ p_{n-1} = \sum_{i=1}^n \frac{p(a_i)}{q'(a_i)}. \]

share|cite|improve this answer
Thanks a lot for a very clear and helpful answer. Completely solved it for me. Have a nice weekend! – user36773 Sep 28 '12 at 11:39

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.